(untitled) (Literary Voice, 2024)
Illness narratives inarguably resonate with the physical and psychological pain experienced by the patients as well as the caregivers because of the impact of illness and social alienation. The act of writing about the tribulations of being ill, as Lacan posits, protects the writer from its more devastating effects; though it is inadequate to eliminate psychosis. Shaheen Bhatt narrates the agonizing ordeal in I’ve Never Been (Un)happier through a metaphorical conceptualisation of the mental disorders she suffers from. When the telling of the lived experience occurs, the writer creates an alternate story in which she plays the dominant role of a protagonist, retrospects the episodes of mood disorders and fantasizes about death. This paper attempts to analyse the significance of the conceptual metaphors corresponding to the pervasive psychological distress and the role of writing in the recovery process.